Organizational Patterns of english and Foreign Texts for Language Teaching: A Contrastive Analysis - Fabiola D. Kurnia (TEFLIN, 2001)
The purpose of this paper is to analyses the organizational patterns of imaginative English and foreign texts in an English speaking community of a mixed cultural literaty work. A contrastive list of foreign English text in Galsorthys Quality and the standard English texts was used as the data. The data were then analysed according to the organizational patterns of sound systems, grammatical structures, vocabulary system, and cultural features. The analysis suggests that foreign English texts offer a source of systematic preliminary study of language. The conversations in the work of literature provides the learners with sample apractice to recognize the standard of language correctness and the non-standard language variations.